Anticancer activity of Nigerian medicinal plants: a review - Franklyn O. Ohiagu; Paul C. Chikezie; Chinwendu M. Chikezie; Christian E. Enyoh (SpringerOpen, 2021)
Abstract Background Cancer is currently the leading cause of death globally and the number of deaths from cancer is on the rise daily. Medicinal plants have been in continuous use over the years for the management of cancer, particularly, in most developing countries of the world including Nigeria. The use of synthetic drugs for the treatment of cancer is often accompanied by toxic side effects. Thus, the alternative use of readily available and inexpensive medicinal plants is the panacea to the toxic side effects associated with synthetic drugs. Main body The present review summarized the anticancer activity of 51 medicinal plants that are widespread in all regions of Nigeria. Furthermore, the proposed anticancer pharmacological actions as well as the anticancer bioactive compounds, the type of cancer cell inhibited, the plant parts responsible for the anticancer activity, and the nature of the extracts used for the studies were discussed in this review. The 51 Nigerian medicinal plants were reported to exhibit anticancer activities of the prostate, cervices, lung, skin, colon, esophagus, blood, ovary, central nervous system/brain, breast, stomach, pancreas, larynx, and kidney. The major classes of bioactive compounds indicated to be responsible for the anticancer activity include the polyphenols, flavonoids, alkaloids, saponins, triterpenes, tannins, and quinones. The major anticancer pharmacological actions of these bioactive compounds were antiproliferative, cytotoxic, cytostatic, antimetastatic, apoptotic, and antioxidative as well as provoked cell cycle arrest, inhibition of angiogenesis and reduction of cancer cell viability. Conclusion The Nigerian medicinal plants can be harnessed to provide for readily available and inexpensive anticancer drugs in the future because the plants reported in this review showed promising anticancer activity.